Pengaruh Citra Destinasi dan Fasilitas terhadap Revisit Intention di Kawasan Lembah Harau - Sagita, Maharani Dwi; Wulansari, Nidia (YASIN, 2023)
This research is motivated by the phenomenon of tourist interest which is suspected by destination image factors and facilities in the Harau Valley area. This type of research is quantitative descriptive research using the causal associative form survey method. The research population amounted to This research is characterized as quantitative descriptive research using causal associative methodology with surveys. The study population amounted to 33,000 respondents per month and a sample of 100 respondents with sampling techniques using purposive sampling. The data collection method of this research is to distribute questionnaires arranged using a Likert scale that has been tested for validity and reliability. Data analysis techniques include normality, multicollinearity, heteroscedasticity tests, and hypothesis testing including multiple linear regression tests. The results of the study explain that destination image and facilities have a significant effect on revisit intention. Descriptively from the results of the respondent's achievement level, the destination image in the Harau Valley area is classified as very good with a total score of 4,039 with an average of 40.39. Facilities in the Harau Valley area are classified as good with a total score of 4,640 with an average of 46.40. Revisit intention in the Harau Valley area is classified as good with a total score of 4,963 with an average of 49.63. The R Square value is 0.220, where the effect of destination image and facilities on revisit intention is 22% while 78% is influenced by other factors.